Promotional Influence Strategy through Social Media and Word of Mouth on Consumer Purchase Decisions in Pindang Sederhana Restaurant Palembang - Nur Jumarni; Siti Komariah; Emilda Emilda (International Journal of Marketing & Human Resource Research, 2023)
This study aims to determine the effect of promotion strategies through social media and word of mouth on consumer purchasing decisions at Pindang Sederhana Restaurant. The technique of collecting data was questionnaires. The technique is employed as an accidental sampling technique, which is a sampling technique based on coincidentally met by the author that can be presented as a sample. The results prove that the promotion strategy has a higher or significant effect than word of mouth on consumer purchasing decisions at the Palembang simple restaurant. The results of the study using the Correlation Coefficient Test (R) obtained a value of 0.595. So it can be concluded that the relationship between the promotional strategy variables and word of mouth has a strong relationship to consumer purchasing decisions. This research is expected to assist restaurants to consider promotional strategies through social media and world of mouth to increase revenue